An examination of the stability of interpersonal hostile‐dominance and its relationship with psychiatric symptomatology and post‐discharge aggression. Issue 4 (6th October 2015) - Podubinski, Tegan; Lee, Stuart; Hollander, Yitzchak; Daffern, Michael
Abstract : The relevance of interpersonal hostile‐dominance (HD) to post‐discharge aggression in mental health patients is unclear. This study assessed whether (1) HD is stable over time; (2) the relationship between HD and positive, negative, disorganized, and excited symptoms is consistent over time; and (3) HD is related to aggression post‐discharge. Two hundred psychiatric inpatients were recruited on admission to hospital; 41 were available for follow‐up at 6 months post‐discharge, including 29 men and 12 women, with an age range of 19–63 ( M = 39.63 years, SD = 12.69 years). Psychiatric symptomatology and interpersonal style were assessed at recruitment and follow‐up; aggression in the community post‐discharge was measured at follow‐up. Results showed that (1) HD was stable over time despite an overall reduction in psychiatric symptoms, (2) HD was positively correlated with symptom severity at both time points, and (3) higher HD, excited symptoms, and positive symptoms measured in the community, and more severe positive symptoms measured in hospital, were associated with aggressive behavior post‐discharge. These results suggest that HD is a risk factor for more severe psychopathology. Furthermore, HD, positive symptoms, and excited symptoms measured in the community act as risk factors for aggressive behavior post‐discharge. As such, treatment planning and risk assessment should consider HD. Aggr. Behav. 42:324–332, 2016. © 2015 Wiley Periodicals, Inc.